Photooxidation of cyclohexene in the presence of SO2: SOA yield and chemical composition - S. Liu; S. Liu; S. Liu; L. Jia; Y. Xu; N. T. Tsona; S. Ge; L. Du; L. Du; L. Du (Atmospheric Chemistry and Physics, 2017)
Secondary organic aerosol (SOA) formation from a cyclohexene ∕ NOx system with various SO2 concentrations under UV light was investigated to study the effects of cyclic alkenes on the atmospheric environment in polluted urban areas. A clear decrease at first and then an increase in the SOA yield was found with increasing SO2 concentrations. The lowest SOA yield was obtained when the initial SO2 concentration was in the range of 30–40 ppb, while higher SOA yield compared to that without SO2 could not be obtained until the initial SO2 concentration was higher than 85 ppb. The decreasing SOA yield might be due to the fact that the promoting effect of acid-catalysed reactions on SOA formation was less important than the inhibiting effect of decreasing OH concentration at low initial SO2 concentrations, caused by the competition reactions of OH with SO2 and cyclohexene. The competitive reaction was an important factor for SOA yield and it should not be neglected in photooxidation reactions. The composition of organic compounds in SOA was measured using several complementary techniques including Fourier transform infrared (FTIR) spectroscopy, ion chromatography (IC), and Exactive Plus Orbitrap mass spectrometer equipped with electrospray interface (ESI). We present new evidence that organosulfates were produced from the photooxidation of cyclohexene in the presence of SO2.